2019
DOI: 10.1186/s40497-018-0137-z
|View full text |Cite
|
Sign up to set email alerts
|

Can street entrepreneurs be Schumpeterian entrepreneurs? The case of food trucks as family firms in an emerging country

Abstract: In times of economic downturn, entrepreneurship discourse returns to the forefront. In this context, in Brazil, there is a new economic and social phenomenon going on: street ventures as family firms. Once marginalized and normally related to informal work, now they perform activities in the market that allow them to offer higher quality products and to reach consumers with higher purchasing power. Aiming to better understand the phenomenon, this study explores the main aspects that characterize entrepreneursh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(69 reference statements)
1
8
0
1
Order By: Relevance
“…Em países latino americanos, como Brasil, o discurso do empreendedorismo na comida de rua está fortemente atrelado ao conceito de inovação no comércio, com o advento do food truck. Matzembacher et al (2019) descreveram que, tais empresas, constituíam, em sua maioria, um modelo de administração familiar, sob supervisão de um chef profissional e despontaram no "mercado" da comida urbana em ascensão global.…”
Section: Tateando Informalidade E Empreendedorismounclassified
“…Em países latino americanos, como Brasil, o discurso do empreendedorismo na comida de rua está fortemente atrelado ao conceito de inovação no comércio, com o advento do food truck. Matzembacher et al (2019) descreveram que, tais empresas, constituíam, em sua maioria, um modelo de administração familiar, sob supervisão de um chef profissional e despontaram no "mercado" da comida urbana em ascensão global.…”
Section: Tateando Informalidade E Empreendedorismounclassified
“…Recent studies have examined the repositioning of hawker food in the modern era (Alfiero et al., 2017; Henderson, 2017; Matzembacher et al., 2019). Alfiero et al.’s (2017) study compared the economic performance of the ‘Traditional Food Truck’ (TFT) with the ‘Gourmet Food Truck’ (GFT), and the results demonstrated that the GFT was more financially efficient than the TFT, directly acknowledging the importance of innovation as a key competitive advantage indicator in the food business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such efficiency was partly attributed to a pioneering menu and food production setup, which are more appealing to consumers. Similarly, another study on food truck businesses in Brazil concluded that a high success rate among innovative food hawkers is usually found in market places where ‘mature consumers’ are more appreciative of innovation (Matzembacher et al., 2019). In this context, ‘mature consumers’ refer to well-educated or ‘seasoned’ consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mobile food trucks offer a rich context for examining how technology is leading social business, highlighting the importance of managing sustainability in the food supply chain. Food trucks are a sound example of this: mobile kitchens ( Matzembacher et al, 2019 ) which use social media technology to bring local producers and suppliers into contact with communities of customers who seek ‘farm to food truck’ sustainable high-quality ready-made dishes ( Anenberg and Kung, 2015 ). Food trucks use a ‘social-local-mobile’ or SO-LO-MO approach – the integration of social technologies (social media platforms and social networking sites), geolocation technologies and mobile commerce/marketing tools – to create a seamless consumer experience and a cohesive brand ( Lichy et al, 2017 ; Kang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%